Ensefalitis - Fitriyani, Fitriyani; Martogi Simalango, Eka Yuliana (Medula, 2024)
Encephalitis is inflammation of the brain parenchyma, usually caused by an infectious agent for through an autoimmune process that may be post infectious, paraneoplastic or idiopathic. Symptoms that can be caused include fever, changes in behavior, personality, cognition and consciousness. Other complaints may also indicate focal neurological deficits, seizures, movement disorders or autonomic instability. Estimates of the incidence of encephalitis worldwide range from 3,5 to 12,3 per 100.000 patients/year. The groups most at risk of encephalitis are the elderly, children under 1 year of age, people with a weak immune system. To diagnose encephalitis, namely lumbar puncture, brain imaging with CT or MRI, EEG, blood tests, brain biopsy. Case: case report Mrs. A, 40 years old with a diagnosis encephalitis based on anamnesis and physical examination as well as support for administration of betahistine 3x24mg, KSR 3x1, Ramipril 1x2,5mg. Dexamethasone Inj/8hours, Ranitidine Inj/12hours, Phenitoin 3x1, Sucralfat syr 3x1, Racikan 3x1 (Paracetamol 500 mg, Ibuprofen 200 mg, Codeine 20 mg), Ericaf 3x1, Depakene syr 2x1, Flunarizine 2x1, Acyclovir 5x1.